Imaging Recommendations for Diagnosis, Staging, and Management of Hepatic and Biliary Tract Cancer - Chatterjee, Argha; Mukhopadhyay, Sumit; Ghosh, Priya; Shah, Diva; Gehani, Anisha; Baheti, Akshay; Gupta, Bharat; Chandra, Aditi; Chaturvedi, Arvind K.; Khoda, Jeevitesh; Patra, Anurima; Lingegowda, Dayananda; Sen, Saugata (Indian Journal of Medical and Paediatric Oncology, 2023)
Major hepatobiliary cancers include hepatocellular carcinoma, gallbladder carcinoma, and cholangiocarcinoma. There are multiple guidelines and recommendations for the imaging evaluation of these cancers. This article reviews and summarizes principles and recommendations of imaging in hepatobiliary cancers. The cross-sectional imaging protocol is similar among these lesions and is discussed at first followed by the separate discussion of each cancer.
Keywords: cholangiocarcinoma; computed tomography; gallbladder carcinoma; hepatocellular carcinoma; magnetic resonance imaging